From Credit Lines to Customer Satisfaction: a Qualitative Review of FinTech Innovations in Small Business Financing - Irawan, Dadang; Benardi, Benardi; Santoso , Seger; Nurhasanah, Sri Utami (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This qualitative literature review examines the impact of FinTech innovations on small business financing, focusing on credit lines and customer satisfaction. The review explores how FinTech platforms have transformed traditional lending by enhancing accessibility, efficiency, and flexibility for small businesses, particularly those underserved by traditional banks. Key findings show that FinTech innovations, such as the use of alternative data for credit assessment and automated risk management, have significantly improved customer experiences by offering faster, more tailored financial solutions. However, challenges remain, including regulatory concerns, the risk of algorithmic bias, the lack of personalized human interaction, and the potential for over-leveraging among small businesses. Despite these limitations, FinTech continues to evolve, offering promising avenues for improving financial inclusion and borrower experiences. The review concludes that while FinTech has positively influenced the small business financing landscape, further research is needed to address regulatory gaps and ensure the sustainable growth of digital lending systems.